African Newsletter on Occupational Health and Safety - Monyo, R A (Finnish Institute of Occupational Health, 1992)
The rapid increase in industrial and environmental noise and the occurrence of noise-induced hearing loss,both in industrialized and developing countries,dictate the urgent need of concentrating on intervention programmes.
Keywords: Health and Safety